Tellurite resistance as a diagnostic marker for Proteus-Morganella-Providencia group infections - Toptchieva, Anna; Hoffman, Paul S. (DALHOUSIE MEDICAL JOURNAL, 2001)
The Proteus-Morganella-Providencia group of bacteria includes a number of important human opportunistic pathogens. The extent of tellurite resistance phenotype among the PMP bacteria was investigated. Additionally, preliminary investigation was conducted into the potential use of screening for tellurite resistance as a rapid and efficient diagnostic test for the infections caused by the PMP bacteria. Twenty-two clinical isolates of Morganella and Providencia displayed both low and high levels of potassium tellurite resistance, suggesting that the tellurite resistance phenotype is an integral feature of the PMP bacterial group. DNA sequences similar to the ter locus of P. mirabilis were identified by Southern blot hybridization in seven of these clinical isolates, which also displayed high level of tellurite resistance. It is hypothesized that at least three distinct Te systems, including that homologous to the ter locus, mediate tellurite resistance in the PMP bacteria. Based on the variable tellurite resistance levels and implied diversity of the underlying genetic determinants, routine screening for tellurite resistance appears to be an unsuitable basis for an informative diagnostic test of the PMP infections.